Practical Experience in Forming Accounting Policies in Accordance with IPSAS by the Russian Universities - Gabdelhakovna Derzayeva, Guzel; Ilfarovich Yakhin, Ilnar (International Journal of Criminology and Sociology, 2022)
This article studies a relatively recent phenomenon for Russian budget accounting - the formation of accounting policies by the Russian educational institutions in accordance with the International Public Sector Accounting Standards. The purpose of the research is to identify the problematic issues that arise during the formation of accounting policies by the Russian universities and to find ways to solve them. Using such methods as analysis and synthesis, comparison, logical and systemic approaches, the author has identified the main problems that arise in the Russian universities when preparing the accounting policies in accordance with International Public Sector Accounting Standards, and suggested ways to solve them. As a result of the research, the article compares the practice of preparing the accounting policies of four Russian universities in order to present the financial statements in accordance with the International Public Sector Accounting Standards, identifies the common problematic issues and suggests ways to solve them. The article draws a conclusion about the similarity of approaches to the formation of accounting policies according to International Public Sector Accounting Standards practice in the Russian universities. The article substantiates the analogy of many problematic issues that arise in this formation, and the identity of ways to solve them.